PONSETI TECHNIQUE FOR MANAGEMENT OF CONGENITAL IDIOPATHIC CLUB FOOT - Shah, Muhammad Qaisar; Khan, Alamzeb; Zardad, Muhammad Shoaib; Iqbal, Rizwana; Ahmed, Sajjad (Journal of Ayub Medical College Abbottabad, 2017)
Background: Clubfoot or congenital talipes equinovarus, is a congenital deformity of the foot. It consists of cavus, adduction, varus and equinus. This is due to medial displacement of navicular and calcaneus around the talus. Talus is in equinus. Medial deviation of the head and neck of talus is due to force of calcaneus on talus. Methods: This descriptive case series study was conducted at Orthopaedic unit, Ayub Teaching Hospital, Abbottabad from 1st August 2015 to 31st January 2016 to determine the frequency of idiopathic clubfoot correction, by using the Ponseti method. A total of 177, unilateral and bilateral clubfeet, from both genders were studied. Patients between age of 2 weeks to 2 years were included in the study. Basic pirani score six (06) who were previously untreated were included in the study. Syndromic patients, previously treated and patients with associated neuro-mascular disorders were excluded from the study. Patients who were corrected with serial castings, were put in foot abduction brace. Those who needed some sort of surgery, underwent surgery. All the data was collected in the proforma and analysed by SPSS version 16.00. Results: A total of 177 clubfeet were included in the study. Mean age of the patients was 10.28±7.45 ranging from 2 weeks 2 years. There were 93 (52.5%) male and 84 (43.5%) female out of total 177 patients. Of these 20 patients were corrected with serial casting only while 150 patients underwent percutaneous tenotomy, which is a minor procedure and done on out -patient department basis. After correction, the feet were put in 70 degree of abduction in abduction brace. Only 7 patients required some sort of surgery, more than tenotomy. Conclusion: Ponseti is very effective, economical and non-invasive way of treating congenital idiopathic clubfoot. only resistant cases may need some sort of extensive surgery. Keywords: Clubfoot; Ponseti method; Pirani score